COLLABORATIVE GOVERNANCE DI DESA SAMBIRATA, KECAMATAN CILONGOK KABUPATEN BANYUMAS (STUDI TENTANG PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BUDIDAYA KAPULAGA) - Marfuah, Sri Rotul; Suryoto, Suryoto Suryoto; Kusumaningsih, Oti Kusumaningsih (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
At the end of 2019 to 2021 the Covid-19 pandemic has stopped several marketing supply chains that are usually carried out by farmers. One of them is Sambirata Village, Cilongok District, where the majority of the population work as farmers. It is the impact of Covid'19 that has given rise to several other problems including: cardamom production is increasing but sales prices are decreasing, cardamom residues are still not managed properly and seriously, village-owned enterprises cannot become economic institutions in terms of capital and marketing, apart from that they have not been able to partner with other agencies to help increase the sale and purchase of cardamom. This study aims to explain and describe how Collaborative Governance in Sambirata Village, Cilongok District, Banyumas Regency in increasing Community Economic Empowerment through Cardamom Cultivation. The method used is descriptive qualitative. The results of this study indicate that Collaborative Governance in Sambirata Village, Cilongok District, Banyumas Regency (a study of community economic empowerment through cardamom cultivation), has not been maximized, but so far the efforts made by the Village Government and Private Government (PT.Sido Muncul) have been sufficient good for helping in efforts to empower the community's economy, both in terms of increasing human resource capacity, as well as the limited facilities and infrastructure. The role of the Department of Agriculture and Food Security of Banyumas Regency in distributing free fertilizer assistance to cardamom and DOM farmers has been carried out, as well as some assistance from PT.Sido Muncul and BRI Bank which provided assistance with cardamom dryers, then reduced fertilizer distribution and there were still many people who Human resources are still lacking in managing cardamom cultivation. AbstraksiPada akhir tahun 2019 hingga 2021 pandemi Covid-19 telah menghentikan beberapa rantai pasok pemasaran yang biasa dilakukan oleh para petani. Salah satunya Desa Sambirata Kecamatan Cilongok yang mayoritas penduduknya berprofesi sebagai petani. Dampak Covid'19 inilah yang menimbulkan beberapa permasalahan lain antara lain: produksi kapulaga meningkat tetapi harga jualnya menurun, ampas kapulaga masih belum dikelola dengan baik dan serius, Badan Usaha Milik Desa tidak dapat menjadi lembaga ekonomi dalam hal permodalan dan pemasaran, selain itu mereka belum bisa bermitra dengan instansi lain untuk membantu meningkatkan jual beli kapulaga. Penelitian ini bertujuan untuk menjelaskan dan mendeskripsikan bagaimana Collaborative Governance di Desa Sambirata Kecamatan Cilongok Kabupaten Banyumas dalam meningkatkan Pemberdayaan Ekonomi Masyarakat melalui Budidaya Kapulaga. Metode yang digunakan adalah deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa Collaborative Governance di Desa Sambirata Kecamatan Cilongok Kabupaten Banyumas (kajian pemberdayaan ekonomi masyarakat melalui budidaya kapulaga), belum maksimal, namun sejauh ini upaya yang dilakukan oleh Pemerintah Desa dan Pemerintah Swasta (PT .Sido Muncul) sudah cukup baik untuk membantu dalam upaya pemberdayaan ekonomi masyarakat, baik dalam hal peningkatan kapasitas sumber daya manusia, maupun keterbatasan sarana dan prasarana. Peran Dinas Pertanian dan Ketahanan Pangan Kabupaten Banyumas dalam menyalurkan bantuan pupuk gratis kepada petani kapulaga dan DOM sudah terlaksana, serta beberapa bantuan dari PT.Sido Muncul dan Bank BRI yang memberikan bantuan alat pengering kapulaga, kemudian berkurang distribusi pupuk dan masih banyak masyarakat yang Sumber Daya Manusianya masih kurang dalam mengelola budidaya kapulaga.